2014
DOI: 10.5935/1678-9741.20140030
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Ricinus communis polymer with addition of calcium carbonate compared to titanium. Experimental study in guinea pigs

Abstract: ObjectiveThe aim of the present investigation was to determine whether the difference in inflammatory tissue reaction between the Riccinus communis (castor) polymer with calcium carbonate and the titanium implant is statistically significant.MethodsThirty-two Cavia porcellus were allocated into four groups of eight animals each. We implanted the two types of materials in the retroperitoneal space of all the animals. They were euthanized at 7, 20, 30 and 40 days after surgery, and an histological study of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…They found that the calcium phosphate composite improves biocompatibility and osseointegration speed. In another experimental study on the biocompatibility of the Ricinus communis polymer with addition of calcium carbonate in comparison to titanium, a recognized biocompatible material, it was evidenced that composite was not statistically different from the titanium implant regarding tissue inflammatory reaction [20] . Another biomaterial used in this work is the latex derived from the rubber tree Hevea brasilienses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the calcium phosphate composite improves biocompatibility and osseointegration speed. In another experimental study on the biocompatibility of the Ricinus communis polymer with addition of calcium carbonate in comparison to titanium, a recognized biocompatible material, it was evidenced that composite was not statistically different from the titanium implant regarding tissue inflammatory reaction [20] . Another biomaterial used in this work is the latex derived from the rubber tree Hevea brasilienses.…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical staining methods as well as immunohistochemical staining methods are described in the literature 55,62‐64 . The histochemical staining methods mainly concentrated on Picro‐Sirius Red and Masson's trichrome staining methods 14,29,31‐38,40,41,43‐47,65‐70 . In this context, Picro‐Sirius Red staining was mostly performed to evaluate organ fibrosis while Masson's trichrome stainings were commonly used to measure biomaterial‐induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were stained with Masson–Goldner's trichrome staining, to differentiate collagen fibers from the surrounding tissue. Masson–Goldner's trichrome staining is widely used for the analysis of fibrosis in organs and for the evaluation of the fibrotic response to biomaterials 14,35,38,40‐47 . As a result of this procedure, collagen fibers appear in a bright green color in bright field light microscopy, which produces excellent contrast for analysis with digital image quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Castor oil presents in its composition 89.5% to 90% triglyceride ricinoleic acid (12-hydroxy-cis-9-octadecenoic acid), whose molecular formula is C 17 H 32 OHCOOH. In the ester bonds of the triglyceride (1st carbon) reactions of hydrolysis, esterification, alcoholysis and, halogenation can occur (Figure 1) [9][10][11][12] .…”
Section: Castor Oil Catalysis and Physicochemical Characterizationmentioning
confidence: 99%